0404 inhibits hepatocellular carcinoma through a p53/miR-34a/SIRT1 positive feedback loop - Caixia Xia (Nature Portfolio, 2017)
Abstract DNA-damaging agents have been used in cancer chemotherapy for a long history. Unfortunately, chemotherapeutic treatment strategies against hepatocellular carcinoma (HCC) are still ineffective. We screened a novel DNA-damaging compound, designated as 0404, by using time-dependent cellular response profiling (TCRP) based on unique DNA-damage characteristics. We used human HCC cell lines and HCC xenograft mouse model to analyze the anti-cancer effects of 0404. Transcriptome and miRNA arrays were used to verify the anti-cancer mechanism of 0404. It was confirmed that p53 signaling pathway was crucial in 0404 anti-cancer activity and the expression of miR-34a, a key tumor-suppressive miRNA, was up-regulated in 0404-treated HepG2 cells. MiR-34a expression was also down-regulated in HCCs compared with corresponding non-cancerous hepatic tissues. We further identified the mechanisms of 0404 in HepG2 cells. 0404 increased miR-34a expression and acylation p53 protein levels and decreased SIRT1 protein levels in a concentration-dependent manner. The sensitivity of HepG2 cells to 0404 was significantly decreased by transfection with miR-34a inhibitors and SIRT1 protein levels were up-regulated by miR-34a inhibition. Our findings show that 0404 is probably an attractive agent for treating HCC, especially in HCC with wide type (WT) p53, through forming a p53/miR-34a/SIRT1 signal feedback loop to promote cell apoptosis.